Synthesis and Structural Studies of Cr(III)and Fe(III) Ternary Complexes - K. Agarwal, Suresh; Chand, Subhash (Asian Journal of Chemistry, 2010)
Ternary complexes of Cr(lll) and Fe(III) with isonitrosoacetophenone- 2-furoic hydrazide/4-chloroisonitrosoacetophenone-2-furoic hydrazide (INAPFH/ClINAPFH) as primary and 1-(o-methoxyanilinomethyl) benzimidazole (MAMB) as co-ligand have been synthesised and characterised by chemical analysis, magnetic, spectral and thermogravimetric studies. Analytical data suggested 1 : 1 : 1 (M-L/L' -L") stoichiometric composition for the isolated complexes [where M = Cr(III)/Fe(III), L = C13H10N3O3, L' = C13H9N3O3CI and L" = C15H15N3O]. The Ωm values of the complexes (178.4-182.6 ohm-1 cm2 mol-1) in DMF at the concentration 10-3 M indicate their 1 : 2 electrolytic nature. Comparison of the IR sepctra of ligands and complexes show that tridentate nature of the hydrazide with oximino and azomethine nitrogeh and carbonyl oxygen as the donor sites and bidentate behaviour of the co-ligand possessing nitrogen atoms of the C=N (benzimidazole ring) and NH as potential donors. Magnetic moments, reflectance spectral bands and values of ligand field parameters show that the complexes possess octahedral stereochemistry. The complexes are thermally stable up to 150°C and a mass-loss corresponding to one molecule of water in 160-180°C temperature range shows the presence of coordinated water in them. At 570-700°C, organic ligands are completeiy lost and stable metallic oxides are obtained.